On the aerodynamical instability of cylindrical bars based on elastic support with viscous restraint - Bich, Nguyen Dang; Thong, Nguyen Vo (Vietnam Journal of Mechanics, 1994)
The aero dynamical instability is a special effect of the self-oscillation phenomenon. The occurrence condition of this effect is the change of the aerodynamic parameters, such as the increase and decrease of the Reynolds coefficients. In this paper the authors present an aerodynamic form, look for an exact solution to the non-linear differential equation with viscous restraint and analyze critical cases leading to the aerodynamic instability. The obtained result gives an idea in exactly solving some non-linear differential equation classes.